2023
DOI: 10.1002/cssc.202201990
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Surface Grafting of Pt Nanocatalysts for Reconciling Methanol Tolerance with Methanol Oxidation Activity

Abstract: A conceptual challenge toward more versatile direct methanol fuel cells (DMFCs) is the design of a single material electrocatalyst with high activity and durability for both oxygen reduction reaction (ORR) and methanol oxidation reaction (MOR). This requires to conciliate methanol tolerance not to hinder ORR at the cathode with a good MOR activity at the anode. This is especially incompatible with Pt materials. We tackled this challenge by deriving a supramolecular concept where surface-grafted molecular ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…6(d)), there is no evident change in the ORR activity using Pd–Cr_350 °C-modified electrode after the injection of methanol in the solution, as proved by nearly the same RDE voltammograms in both O 2 -saturated 0.1 M KOH with and without methanol; however, the Pt/C were highly affected by the presence of methanol which was highly susceptible to methanol poisoning. 62,63 This result, therefore, demonstrated that Pd–Cr_350 °C is an excellent methanol tolerant cathodic catalyst for alkaline oxygen reduction. In addition, the alkaline ORR activity of Pd–Cr_350 °C revealed a remarkable achievement, exhibiting a comparable or even superior level of performance when compared to state-of-the-art Pd-based nanomaterials that have been previously reported (Table S1†).…”
Section: Resultsmentioning
confidence: 69%
“…6(d)), there is no evident change in the ORR activity using Pd–Cr_350 °C-modified electrode after the injection of methanol in the solution, as proved by nearly the same RDE voltammograms in both O 2 -saturated 0.1 M KOH with and without methanol; however, the Pt/C were highly affected by the presence of methanol which was highly susceptible to methanol poisoning. 62,63 This result, therefore, demonstrated that Pd–Cr_350 °C is an excellent methanol tolerant cathodic catalyst for alkaline oxygen reduction. In addition, the alkaline ORR activity of Pd–Cr_350 °C revealed a remarkable achievement, exhibiting a comparable or even superior level of performance when compared to state-of-the-art Pd-based nanomaterials that have been previously reported (Table S1†).…”
Section: Resultsmentioning
confidence: 69%
“…20 Despite the above successful preparation of porous Pt nanomaterials, the construction of Pt catalysts with well-controlled dimensions and morphologies continues to be highly challenging. 21 There is thus a strong desire to develop new options to overcome the tediousness and complexities of these synthetic methods. In addition, the development of electrocatalysts displaying good reactivity and robust reliability at low PGM loading to afford high performance in particular applications is also regarded as an urgent need.…”
mentioning
confidence: 99%